2008
DOI: 10.1007/s10646-008-0247-4
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of dimethyl carboxylic phthalate ester by Burkholderia cepacia DA2 isolated from marine sediment of South China Sea

Abstract: Burkholderia cepacia DA2, isolated from marine sediment of the South China Sea, is capable of utilizing dimethyl phthalate (DMP) as the sole source of carbon and energy. During the transformation of DMP in batch culture, its corresponding degradation intermediates were identified as monomethyl phthalate (MMP) and phthalate acid (PA) sequentially over the time of incubation. The biodegradation biochemical pathway of DMP was DMP to MMP and then to PA before mineralization. Degradation of DMP by B. cepacia DA2 wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 43 publications
3
30
0
Order By: Relevance
“…The substrate utilization profile (Table 2) suggested that the isolates might degrade PAEs through different pathways. Furthermore, we found that the efficiency of DMP degradation by representative strains was much higher than that reported previously (Wang et al 2008b). These results indicate the biotechnological potential of these isolates for bioremediation.…”
Section: Discussionsupporting
confidence: 43%
“…The substrate utilization profile (Table 2) suggested that the isolates might degrade PAEs through different pathways. Furthermore, we found that the efficiency of DMP degradation by representative strains was much higher than that reported previously (Wang et al 2008b). These results indicate the biotechnological potential of these isolates for bioremediation.…”
Section: Discussionsupporting
confidence: 43%
“…Other studies emphasize marine environments [86][87][88][89], natural soils [90,91], and river water [86,92,93]. In addition, enzymatic assays have been used to assess degradability of a specific polymer under laboratory conditions [86,[94][95][96] or to detect specific enzyme activity indicative of a degradative process, for example, esterases [12,[97][98][99][100][101][102][103][104][105][106][107][108][109][110][111][112]. Experiments in situ always suffer from poor reproducibility because of the broad range of variables involved [83,84] and the difficulty in interpretation of experimental results and extrapolation of possible mechanisms involved.…”
Section: Degradation Processesmentioning
confidence: 99%
“…Polymeric materials are known to contain a wide array of chemicals, including plasticizers to improve their processibility and product quality; these plasticizers mostly include phthalate esters, specifically dimethyl phthalate esters (namely ortho-dimethyl phthalate ester, dimethyl isophthalate ester, and dimethyl terephthalate ester), di-n-butyl phthalate ester, and dibutylbenzyl phthalate ester [12,[101][102][103][104][105][106][107][108][109][110][111][112]. Since these chemicals are not covalently bound to the polymer resins, they can be utilized by many bacteria isolated from activated sludge [211], mangrove sediments [101][102][103][104][105]108] and deep-ocean sediment [12,106,107] (Table 30.4).…”
Section: G Plasticizersmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a biocide for protection of polymeric coatings should be tested in the proposed coating materials and exposed under the relevant conditions [5,6]. Polymeric materials also contain plasticizers which can be utilized by microorganism as a source of carbon and energy [163,164]. Such growth-promoting effects of chemicals leaching from these materials can sustain levels of microbial activity and growth not seen in culture solutions.…”
Section: C35 Corrosion and Deteriorationmentioning
confidence: 99%